The Eye is the Lamp of the Body (Matthew 6.22–23=Luke 11.34–36) - Allison, Dale C. 1955- (1987)
The most significant recent contribution to the understanding of Matt 6. 22–23 (= Luke 11. 34–36: Q) comes from Hans Dieter Betz. In his article on ‘Matthew vi.22f. and ancient Greek theories of Vision’ Betz claims to find in the pre-Socratics, in Plato, and in Philo the clues by which the enigmatic logion about the eye as the lamp of the body can best be elucidated. He directs attention to the following texts in particular: (1) Plato, Timaeus 45B–46A. In discussing the creation of the human body by the gods, Plato speaks of the ‘light-bearing eyes’(φωσφόραμματα), and he asserts that, within the human eye, there is a type of fire, a fire which does not burn but is, as Bury translates, ‘mild’. When we see, this fire, which is both ‘pure’ (είλıκρωές) and ‘within us’ (έντòς ὴμῶν), flows through the eyes and out into the world, where it meets the light of day. Now since like is attracted to like, the light of the eyes coalesces with the light of day, forming one stream of substance. And then, to quote Plato, ‘This substance, having all become similar in its properties because of its similar nature, distributes the motions of every object it touches, or whereby it is touched, throughout all the body, even unto the soul, and brings about the sensation which we term seeing.’ In fine, we see because we have within us a light that streams forth through our eyes.